Detection and Isolation of Clostridium difficile Asymptomatic Carriers During Clostridium difficile Infection Outbreaks: An Exploratory Study. (16th May 2018) - Paquet-Bolduc, Bianka; Gervais, Philippe; Roussy, Jean-Francois; Trottier, Sylvie; Oughton, Matthew; Brukner, Ivan; Longtin, Jean; Loo, Vivian G; Dascal, Andre; Longtin, Yves
Abstract: During 4 Clostridium difficile infection outbreaks, unit-wide screening of 114 patients led to detection and isolation of 15 (13%) C. difficile asymptomatic carriers. Carriage prevalence varied between outbreaks, from 0% to 29% ( P = .004). Isolating carriers was not associated with significantly shorter outbreak durations, compared with historical controls.